Pengembangan Strategi Pembelajaran Kolaboratif Dalam Meningkatkan Keterampilan Sosial - Gina Alyanti Ramadhani (Prodi PGSD Unsultra, 2024)
Collaborative learning is an approach that involves students working together to achieve common learning goals. The purpose of this study is to explore the development of collaborative learning strategies that can improve students' social skills in elementary schools. This literature review identifies various models and approaches in collaborative learning that focus on developing communication, empathy, and cooperation between students. The results of this study indicate that the implementation of well-planned collaborative learning can significantly improve students' social skills. These findings provide insights for educators in designing learning strategies that not only develop academic skills but also students' social skills that are essential for their lives.